Shooting dynamics in archery - Erkek, M.; Tinazci, C. (IFMBE Proceedings 31. 6th World Congress of Biomechanics (WCB 2010), 1 - 6 August 2010, Singapore, 2010)
The purpose of this study is to investigate the relationships between physiological and mechanical dynamics during arrow releasing in archery with the quality of the arrow shot. Four elite female archers were involved in this study.